2009
DOI: 10.1128/aac.00314-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Murine Efficacy and Toxicity Studies of Nebulized SCC1, a Methylated Caffeine-Silver(I) Complex, for Treatment of Pulmonary Infections

Abstract: The expanding clinical challenge of respiratory tract infections due to resistant bacteria necessitates the development of new forms of therapy. The development of a compound composed of silver coupled to a methylated caffeine carrier (silver carbene complex 1 [SCC1]) that demonstrated in vitro efficacy against bacteria, including drug-resistant organisms, isolated from patients with respiratory tract infections was described previously. The findings of current in vitro studies now suggest that bactericidal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
(44 reference statements)
3
44
1
Order By: Relevance
“…Youngs et al have reported NHC-silver complexes derived from 4,5-dichloro-1H-imidazole, which show anticancer activity against the human cancer cell lines OVCAR-3 (ovarian), MB157 (breast), and HeLa (cervical) [5]. Furthermore led the synthesis and antimicrobial evaluation of NHC silver complexes derived from 1-benzyl-3-tert-butylimidazole by Ghosh et al to another important contribution [8]. Additionally a larger number of known compounds were evaluated as potential antibiotics by Roland and Jolivalt [9].…”
Section: Introductionmentioning
confidence: 95%
“…Youngs et al have reported NHC-silver complexes derived from 4,5-dichloro-1H-imidazole, which show anticancer activity against the human cancer cell lines OVCAR-3 (ovarian), MB157 (breast), and HeLa (cervical) [5]. Furthermore led the synthesis and antimicrobial evaluation of NHC silver complexes derived from 1-benzyl-3-tert-butylimidazole by Ghosh et al to another important contribution [8]. Additionally a larger number of known compounds were evaluated as potential antibiotics by Roland and Jolivalt [9].…”
Section: Introductionmentioning
confidence: 95%
“…designed a library of N -heterocyclic silver carbene complexes (SCCs), which improved the stability of Ag + to light and aqueous solution, allowed for the direct administration of silver-compounds via nebulization, and demonstrated the antimicrobial activity of Ag + against contemporary Gram-positive and Gram-negative pathogens. 1624 In parallel, Cannon and Youngs et al demonstrated sustained silver release and potent in vitro and in vivo antimicrobial efficacy of SCC10-bearing L-tyrosine polyphosphate nanoparticles (LTP NPs) against the cystic fibrosis pathogen Pseudomonas aeruginosa . 25 Meanwhile, benefiting from polymeric backbone-structured building blocks with precisely controlled architectures, surface characteristics and supramolecular assembly, 26, 27 Cannon, Youngs and Wooley et al highlighted the preparation of smaller particle size and the introduction of functionalities for attachment of targeting moieties by utilizing multifunctional shell cross-linked knedel-like polymeric nanoparticles (SCK NPs) of poly(acrylic acid)- block -polystyrene (PAA- b -PS).…”
mentioning
confidence: 99%
“…Several NHC-silver complexes were used in in vivo studies to treat multidrug-resistant pulmonary infections found in cystic fibrosis patients [92], and in vitro and in vivo studies on several strains of cancerous cells [93].…”
Section: Nhc-silver Complexesmentioning
confidence: 99%